Reynolds numbers exhibit dramatic influence on directionality of movement of self-propelled systems - Zhao, Guanjia (2013)
Self-propelled artificial objects are at the current forefront of research. We demonstrate here that the motion directionality of millimetre sized self-propelled objects is highly dependent on the Reynolds numbers (Re) of the systems, with emphasis on the “intermediate” Re region (1–600). Our findings have strong implication on the motion controllability and predictability of these independent self-propelled systems.